PENINGKATAN KETERAMPILAN BERDISKUSI MELALUI STRATEGI ELVES (EXCITE, LISTEN, VISUALIZE, EXTEND, AND SAVOR) PADA SISWA KELAS VIII F SMP NEGERI 1 SELAT KUALA KAPUAS - Melania Sugiyarti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This research aims to improve the skills of discussion grade VIII F SMP Negeri 1 Strait by using strategies of ELVES (Excite, Listen, Visualize, Extend, and Savor). Through a strategy of ELVES (Excite, Listen, Visualize, Extend, and Savor), an increase can be seen in the process as well as in products.This type of research this is a class action research (PTK). The research was carried out in junior high Country with the subject Straits 1 is grade VIII F, consisting of 35 students. Collaboration between researchers with English subjects in this study for three sikus. Techniques used include data collection, observation, interview, a skills test, and discuss the Notes field. Research instrument used is a sheet of observation, interview guidelines, notes field, and discussion skills assessment sheets students.The results showed that, the use of strategies of ELVES (Excite, Listen, Visualize, Extend, and Savor) can improve learning skills in discussing grade VIII F SMP Negeri 1 Strait. The increase shown from the quality of the learning process that reflected the spirit of learning, students ' attention towards learning, active students, the learning process, and the opportunity to speak. The increase in products can be seen from the average score of pratindakan discussion skills until the cycle III. On pratindakan, score an average of 8.09 earned class, then increased to 14.03 on cycle I and cycle II 18.77. The last increase occurred in cycle III i.e. be 21.52. An increase in the average score of the cycle I to III of 7.49 cycle, while the average score of the class from pratindakan to cycle III of 13.43.